Directly measured second hand smoke exposure and asthma health outcomes. Issue 10 (28th September 2005) - Eisner, M D; Klein, J; Hammond, S K; Koren, G; Lactao, G; Iribarren, C
Abstract : Background: Because they have chronic airway inflammation, adults with asthma could have symptomatic exacerbation after exposure to second hand smoke (SHS). Surprisingly, data on the effects of SHS exposure in adults with asthma are quite limited. Most previous epidemiological studies used self-reported SHS exposure which could be biased by inaccurate reporting. In a prospective cohort study of adult non-smokers recently admitted to hospital for asthma, the impact of SHS exposure on asthma health outcomes was examined. Methods: Recent SHS exposure during the previous 7 days was directly measured using a personal nicotine badge (n = 189) and exposure during the previous 3 months was estimated using hair nicotine and cotinine levels (n = 138). Asthma severity and health status were ascertained during telephone interviews, and subsequent admission to hospital for asthma was determined from computerised utilisation databases. Results: Most of the adults with asthma were exposed to SHS, with estimates ranging from 60% to 83% depending on the time frame and methodology. The highest level of recent SHS exposure, as measured by the personal nicotine badge, was related to greater asthma severity (mean score increment for highest tertile of nicotine level 1.56 points; 95% CI 0.18 to 2.95), controlling for sociodemographic covariates and previous smoking history. Moreover, the second and third tertiles of hair nicotine exposure during the previous month were associated with a greater baseline prospective risk of hospital admission for asthma (HR 3.73; 95% CI 1.04 to 13.30 and HR 3.61; 95% CI 1.0 to 12.9, respectively). Conclusions: Directly measured SHS exposure appears to be associated with poorer asthma outcomes. In public health terms, these results support efforts to prohibit smoking in public places.